Oceans in glass [videorecording (DVD)] : behind the scenes of the Monterey Bay Aquarium - Coyote, Peter (Nature video library., 2006)
Explore the Monterey Bay Aquarium, a modern marvel with stunning displays and more than 35,000 animals and plants in presentations of complete habitats. See how the aquarium creates its displays, the conservation and research efforts they undertake, and how they deal with a guest great white shark.